THE ACTION OF PARASECURITY STRUCTURES AND FOREIGN FACTORS IN KOSOVO AND METOHIA IN THE HYBRID WAR AGAINST THE REPUBLIC OF SERBIA - Hatidza, Berisa Alil; Petrović, Dejan B. (The Policy of National Security, 2026)
This paper examines a broader context of the expressed interests of certain foreign factors in contemporary security circumstances, characterised by the presence of hybrid threats, aiming to observe the position and relevance of the Autonomous Province of Kosovo and Metohija (AP of Kosovo and Metohija) within the security agenda of these forces. The purpose of the analysis is the improvement of the methodological approach to a more objective perception and strategic comprehension of the activities and intentions, as well as the accentuation of the significance attributed by the great powers to that territory within the context of other areas and issues where their interests are confronted. The paper analyzes the interests of the United States (US) as the main foreign policy actor in KiM, as well as the interests of certain great and regional powers with a longer presence in the Balkan region, such as the Russian Federation (RF), the Federal Republic of Germany, the United Kingdom of Great Britain and Northern Ireland (UK), and the Republic of Turkey. In order to pursue their own interests and project influence, foreign factors have been undertaking a whole array of diverse measures and activities that are in our contemporary analyses in the field of defence and security often called hybrid warfare, therefore this paper provides a brief review of the hybrid warfare concept through the evaluation of prominent questions and responses, graded as relevant to the decision-making authorities on the strategic level, along with the description of the specific hybrid activities performed by certain para-security structures and foreign factors in the case of the AP of Kosovo and Metohia.
Keywords: hybrid war; para-security structures; foreign factor; NATO; Kosovo and Metohija